W poszukiwaniu śladów przeszłości – komiks jako medium małej i wielkiej historii (przykład powieści graficznych Nie pojedziemy zobaczyć Auschwitz Jérémiego Dresa i Zaduszki Rutu Modan) - Czaja, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
In Search of Traces of the Past: Comics as a Medium for History Great and Small The analysis of the article’s author focuses on the graphic novels The Property by Rutu Modan and We Won’t See Auschwitz by Jérémy Dres. Th e comics discussed deal with similar issues. Both refer to the wartime and postwar fate of Polish Jews, show military history as a factor shaping the family history of multiple generations, and touch upon issues concerning identity, Polish-Jewish relations, and national stereotypes. Through the use of comics, both authors try to preserve pieces of family history while touching upon many far more general and universal issues. Comics prove in this case to be a handy tool in the telling of intertwining histories great and small.